THE CONCEPT AND LEGAL POLITICS OF DISCRETION AS FREEDOM OF ACTION FOR GOVERNMENT OFFICIALS - PURWANTO, DEDI; Abdul Aziz Nasihuddin; Siti Kunarti (Fakultas Hukum, Universitas Samudra, 2024)
Government administration encompasses, at the very least, the procedures involved in decision-making and/or actions taken by government bodies and/or officials. This is closely related to the legal policy within the Omnibus Law on Job Creation. Therefore, the Omnibus Law on Government Administration is one of the 79 laws amended through the Omnibus Law on Job Creation. Through the Omnibus Law on Job Creation, the requirement for discretion to be